KONSEP TEOLOGIS AHLUSUNAH WALJAMAAH DALAM TUHFAH AR-RAAGHIBIIN KARYA ABDUSSAMAD AL-PALIMBANI (SEBUAH KAJIAN FILOLOGIS) - Ahmad Taufiq; Bagus Kurniawan; Asep Yudha Wirajaya; Istadiyantha Istadiyantha (Universitas Sebelas Maret, 2020)
Tuhfah ar-Raaghibiin is a Classical Malay text which is still in a manuscipts. This text contains Abdussamad al-Palimbani’s intelectual thought on theology field written on 1128 H. This study aims to describe Ahlusunah Waljamaah concept and other theology concepts. After catalog study was carried out in Indonesia, it can be implied that there is one manuscript coded Ml. 719 saved in Perpustakaan Nasional Jakarta. The approach used in this research is textual-formal. The data was collected with library technique. The technique to analyse these data is content analysis dan comparative analysis. Ahlusunah Waljamaah concept on Tuhfah ar-Raaghibin compromises two extreme concepts, those are between Jabbariyah and Qadariyah, between Rafidliyah and Kharijiyah, and between Jahmiyyah and Murji’ah. Rafidliyah believes in Ali’s majesty and claims Kafir to his enemies. Jabbariyah argues that human actions are created by God. On the other hand, Qadariyah argues that human actions are held by themself. Furthermore Jahmiyyah considers on God purification and justice. Moreover Murji’ah trust on omnipotence of God.